2020
DOI: 10.1111/jfbc.13343
|View full text |Cite
|
Sign up to set email alerts
|

Antihemorrhoidal activity of organic acids ofCapsella bursa‐pastorison croton oil‐induced hemorrhoid in rats

Abstract: This study was aimed to investigate the antihemorrhoidal effects of ethanol (CBE) and water extracts (CBW) of Capsella bursa‐pastoris, an edible plant and a precipitant (CBW‐1) obtained from the CBW in croton oil (CO)‐induced hemorrhoid model in rats. CBW‐1 was contain three organic acids, citric acid (36.09%), malic acid (35.56%), and quinic acid (17.73%). Hemorrhoids were evaluated by histopathology of recto‐anal tissues and biochemical parameters in plasma and recto‐anal tissues of rats. CBW, CBE, and CBW‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…12 Additionally, it was reported that Capsella bursa-pastoris plays a role in the biosynthesis of several active substances, including tannins, sulforaphanes, tyramines, sterols, flavonoids, choline, acetylcholine, and histamine. 3,20,25 Apaydin Yildirim et al 3 demonstrated the anti-hemorrhoidal effects of ethanol and water extracts of Capsella bursapastoris on croton oil-induced hemorrhoids in rats. Accordingly, Capsella bursa-pastoris reduced the severity of hemorrhagic necrotic enteritis and the levels of cytokines and lipid peroxidation in serum, as well as myeloperoxidase and anti-oxidants in the recto-anal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12 Additionally, it was reported that Capsella bursa-pastoris plays a role in the biosynthesis of several active substances, including tannins, sulforaphanes, tyramines, sterols, flavonoids, choline, acetylcholine, and histamine. 3,20,25 Apaydin Yildirim et al 3 demonstrated the anti-hemorrhoidal effects of ethanol and water extracts of Capsella bursapastoris on croton oil-induced hemorrhoids in rats. Accordingly, Capsella bursa-pastoris reduced the severity of hemorrhagic necrotic enteritis and the levels of cytokines and lipid peroxidation in serum, as well as myeloperoxidase and anti-oxidants in the recto-anal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Its leaves and roots can be eaten both raw and cooked. 3 The tea formulations made from the whole plant or the dried herb have been used for different purposes. 2 In addition to its hemostatic and oxytocic properties, Capsella bursa-pastoris is also known for its anti-oxidant, anti-inflammatory, anti-ulcer, and in-vivo anti-cancer activities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations